High-resolution seismic reflection exploration for evaluating the seismic hazard in a Plio-Quaternary intermontane basin (L'Aquila downtown, central Italy). (10th November 2019) - Tallini, Marco; Spadi, Marco; Cosentino, Domenico; Nocentini, Marco; Cavuoto, Giuseppe; Di Fiore, Vincenzo
Abstract: On April 6, 2009, a Mw 6.1 earthquake struck the Plio-Quaternary intermontane L'Aquila-Scoppito Basin in central Italy, causing severe damage to L'Aquila historical downtown and surroundings, which were affected by notable site effects. Previous work has suggested that different site effects may be related to the complex subsurface geologic architecture, given the variable thickness and lithology of L'Aquila-Scoppito Basin filling deposits, on top of which the city was built. To improve the 3D geological model of L'Aquila downtown for seismic site response evaluation and to estimate the seismic hazard of possible buried active normal faults, a multitask project was carried out consisting mainly of the integration of surface geology, geological subsurface datasets and geophysical surveys. Data were interpreted with the aim of creating and building a detailed stratigraphic and tectonic model for the Plio-Quaternary cover of the continental basin and the buried morphology of the Meso-Cenozoic bedrock. We discuss and interpret the results concerning a 1 km-long high-resolution seismic reflection profile and refraction tomography integrated with stratigraphy from deep and shallow boreholes. The results allowed the reconstruction of the Plio-Quaternary succession below L'Aquila downtown. The Plio-Quaternary basin depocentre is located in a minor NNW-SSE graben, an extensional structure within the main regional graben that borders L'Aquila-Scoppito Basin. Finally, data interpretation allowed us to define the subsoil geological model of the study area, to evidence the recent activity of several faults, and to reconstruct the Plio-Quaternary tectono-stratigraphic evolution of the basin. Together, the data are useful to evaluate the seismic hazard of cities with great cultural heritage of central Italy, such as the case study of L'Aquila downtown.